2015
DOI: 10.1128/aem.03292-14
|View full text |Cite
|
Sign up to set email alerts
|

XoxF-Type Methanol Dehydrogenase from the Anaerobic Methanotroph “Candidatus Methylomirabilis oxyfera”

Abstract: b "Candidatus Methylomirabilis oxyfera" is a newly discovered anaerobic methanotroph that, surprisingly, oxidizes methane through an aerobic methane oxidation pathway. The second step in this aerobic pathway is the oxidation of methanol. In Gramnegative bacteria, the reaction is catalyzed by pyrroloquinoline quinone (PQQ)-dependent methanol dehydrogenase (MDH). The genome of "Ca. Methylomirabilis oxyfera" putatively encodes three different MDHs that are localized in one large gene cluster: one so-called MxaFI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 70 publications
1
59
0
Order By: Relevance
“…In 2012, this was resolved when Nakagawa et al demonstrated that MeDH, purified from M. extorquens AM1 cells grown in medium containing La, consisted of a XoxF dimer containing 1.24 atoms of La and lacked Ca (11). Since these findings, XoxF has been purified from a variety of methylotrophs, displaying differences in subunit composition, optimal enzyme assay parameters, and oxidation products depending on the organism studied (9,10,25). In 2014, Pol et al addressed the biochemical promiscuity of XoxF MeDHs by determining that a variety of lanthanides, including La, Ce, Pr, and Nd, could support methanol-dependent growth of Methylacidiphilum fumariolicum SolV (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, this was resolved when Nakagawa et al demonstrated that MeDH, purified from M. extorquens AM1 cells grown in medium containing La, consisted of a XoxF dimer containing 1.24 atoms of La and lacked Ca (11). Since these findings, XoxF has been purified from a variety of methylotrophs, displaying differences in subunit composition, optimal enzyme assay parameters, and oxidation products depending on the organism studied (9,10,25). In 2014, Pol et al addressed the biochemical promiscuity of XoxF MeDHs by determining that a variety of lanthanides, including La, Ce, Pr, and Nd, could support methanol-dependent growth of Methylacidiphilum fumariolicum SolV (8).…”
mentioning
confidence: 99%
“…A key step in this process is the oxidation of methanol to formaldehyde, which is carried out by different enzymes, including methanol dehydrogenase (MeDH) and alcohol oxidase, depending on the specific methylotroph (6,7). Recently, it was discovered that some types of MeDHs require rareearth elements, specifically lanthanides, as cofactors (8)(9)(10)(11) [Yb], and lutetium [Lu]) and two chemically similar elements (scandium [Sc] and yttrium [Y]). The term "rare earth" is deceptive, as these lanthanide elements are relatively abundant in the Earth's crust, found at levels similar to those seen for copper and zinc (Ce, 66 ppm; La 39 ppm; Cu, 60 ppm, Zn, 70 ppm) (12).…”
mentioning
confidence: 99%
“…It was initially believed that this enzyme was critical for methylotrophic growth on methanol since no methanol dehydrogenase activity was observed in mutants defective in the production of this protein (24). Subsequently, however, it was found that there is a homolog to the large subunit, termed XoxF, with 50% sequence identity to MxaF (25,26). This also encodes a PQQ-dependent methanol dehydrogenase that is associated with the periplasm (26, 27) but appears to be composed only of a single subunit with a predicted mass of 65 kDa (28) or associated with the small subunit of MxaI (26), depending on the microbe.…”
mentioning
confidence: 99%
“…This also encodes a PQQ-dependent methanol dehydrogenase that is associated with the periplasm (26, 27) but appears to be composed only of a single subunit with a predicted mass of 65 kDa (28) or associated with the small subunit of MxaI (26), depending on the microbe. Further, it is often observed that multiple homologs of XoxF are found in the genome of a variety of methylotrophs and methanotrophs (25,26,29,30).…”
mentioning
confidence: 99%
“…Together, these suppositions suggest that XoxFtype MDHs may be the primary MDHs for methylotrophy. For the few that have been studied to date, production of functional XoxF-type MDHs requires the presence of lanthanides in the growth medium (23)(24)(25)(26)(27) and all reported XoxF-type MDHs that have been biochemically characterized thus far contain a lanthanide such as cerium (Ce 3ϩ ) or lanthanum (La 3ϩ ), rather than Ca 2ϩ in the active site (25,27). Limited kinetic studies of XoxFtype MDHs have shown an increased efficiency when oxidizing methanol compared to that of MxaFI-type MDHs (summarized in reference 22).…”
mentioning
confidence: 99%